Examining the use of process evaluations of randomised controlled trials of complex interventions addressing chronic disease in primary health care—a systematic review protocol. Issue 1 (December 2016) - Liu, Hueiming; Muhunthan, Janini; Hayek, Adina; Hackett, Maree; Laba, Tracey-Lea; Peiris, David; Jan, Stephen
Abstract Background Randomised controlled trials (RCTs) of complex interventions in primary health care (PHC) are needed to provide evidence-based programmes to achieve the Declaration of Alma Ata goal of making PHC equitable, accessible and universal and to effectively address the rising burden from chronic disease. Process evaluations of these RCTs can provide insight into the causal mechanisms of complex interventions, the contextual factors, and inform as to whether an intervention is ineffective due to implementation failure or failure of the intervention itself. To build on this emerging body of work, we aim to consolidate the methodology and methods from process evaluations of complex interventions in PHC and their findings of facilitators and barriers to intervention implementation in this important area of health service delivery. Methods Systematic review of process evaluations of randomised controlled trials of complex interventions which address prevalent major chronic diseases in PHC settings. Published process evaluations of RCTs will be identified through database and clinical trial registry searches and contact with authors. Data from each study will be extracted by two reviewers using standardised forms. Data extracted include descriptive items about (1) the RCT, (2) about the process evaluations (such as methods, theories, risk of bias, analysis of process and outcome data, strengths and limitations) and (3) any stated barriers and facilitators to conducting complex interventions. A narrative synthesis of the findings will be presented. Discussion Process evaluation findings are valuable in determining whether a complex intervention should be scaled up or modified for other contexts. Publishing this protocol serves to encourage transparency in the reporting of our synthesis of current literature on how process evaluations have been conducted thus far and a deeper understanding of potential challenges and solutions to aid in the implementation of effective interventions in PHC beyond the research setting. Systematic review registration PROSPEROCRD42016035572